2012
DOI: 10.1001/2012.jama.11374
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Omega-3 Fatty Acid Supplementation and Risk of Major Cardiovascular Disease Events

Abstract: Context Considerable controversy exists regarding the association of omega-3 polyunsaturated fatty acids (PUFAs) and major cardiovascular end points.Objective To assess the role of omega-3 supplementation on major cardiovascular outcomes. Data Sources MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials through August 2012.Study Selection Randomized clinical trials evaluating the effect of omega-3 on allcause mortality, cardiac death, sudden death, myocardial infarction, and stroke.Data Extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
564
2
18

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 892 publications
(604 citation statements)
references
References 46 publications
20
564
2
18
Order By: Relevance
“…These results are consistent with other rodent studies indicating that nutraceutical supplements have no effect on lifespan, or shorten it (Ristow and Schmeisser 2011;Selman et al 2013;Spindler et al 2013b). Our results also are consistent with studies of initially healthy humans indicating that the use of dietary supplements is associated with either no effect or a negative effect on survival (e.g., Bjelakovic et al 2004; Chowdhury et al Macpherson et al 2013;Miller et al 2005;Myung et al 2013;Rizos et al 2012). While some supplements may be effective in treating specific disease states, most data suggest that either simple or complex combinations of supplements are not effective in delaying the onset or progress of the major causes of death in mice or humans.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with other rodent studies indicating that nutraceutical supplements have no effect on lifespan, or shorten it (Ristow and Schmeisser 2011;Selman et al 2013;Spindler et al 2013b). Our results also are consistent with studies of initially healthy humans indicating that the use of dietary supplements is associated with either no effect or a negative effect on survival (e.g., Bjelakovic et al 2004; Chowdhury et al Macpherson et al 2013;Miller et al 2005;Myung et al 2013;Rizos et al 2012). While some supplements may be effective in treating specific disease states, most data suggest that either simple or complex combinations of supplements are not effective in delaying the onset or progress of the major causes of death in mice or humans.…”
Section: Discussionsupporting
confidence: 90%
“…The active ingredient in fish is believed to be long-chain n-3 PUFA which are abundant in fatty fish, such as anchovies, herring, salmon (both farmed and wild), mackerel, sardines, trout and white tuna (22) . However, findings from RCT (mostly secondary prevention studies) have indicated a much weaker degree of reduction in risk of cardiac death (9 %) when subjects were given marine n-3 PUFA (23) .…”
Section: Cvdmentioning
confidence: 99%
“…Among these 59 surrogate endpoint trials that had a subsequent clinical endpoint trial, in 24 cases the clinical endpoint trial results validated the positive surrogate trials, while in 20 the subsequent clinical endpoint trial was negative (Table 3). 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 A negative surrogate endpoint trial was less likely to be followed by a positive outcome trial and we identified only 3 such examples ( P =0.02, Figure 2). …”
Section: Resultsmentioning
confidence: 99%